Preparation method of ultralow-expansion optical glass
By selecting the matrix material of the low -thermal expansion coefficient, the introduction of nano -grade oxide particles, and using a multi -stage annealing process and polishing or coating treatment to prepare ultra -low expansion optical glass, solve the problem of high thermal expansion coefficient of the existing optical glass material, and achieve realization, realize the realization The effect of stable glass size under temperature changes.
Patent Information
- Application Number
- CN202411258295.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-28
AI Technical Summary
The thermal expansion coefficient of existing optical glass materials is high, resulting in significant dimensional changes in environments with large temperature changes, affecting the accuracy and stability of the equipment.
By selecting the matrix material of the low -thermal expansion coefficient, the introduction of nano -grade oxide particles, and using a multi -stage annealing process and polishing or coating treatment to prepare ultra -low expansion optical glass.
The extremely low thermal expansion coefficient (at the level of 10^-7/° C) of the glass is achieved, which ensures that the glass has almost no size changes under temperature changes, and it is suitable for high-precision optical components and scientific instruments.
Smart Images

Figure CN119371100A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of optical material and precision instrument manufacturing, in particular to a method for preparing ultra-low expansion optical glass. Background Art
[0002] In the field of modern optics and precision instrument manufacturing, the thermal expansion characteristics, optical uniformity, mechanical strength, and weather resistance of optical glass materials directly affect the accuracy and stability of the equipment. However, the optical glass materials used in the prior art still have deficiencies in certain key performance aspects, which limits their effectiveness in high-precision, high-stability applications.
[0003] Traditional optical glass materials, such as ordinary silicate glass, have good optical properties, but their thermal expansion coefficient is high (usually on the order of 10^-6 / ℃). In an environment with large temperature changes, this type of glass will undergo significant dimensional changes, causing focus drift in the optical system or stress between mechanical components, affecting the accuracy of the equipment. This dimensional instability limits their use in application scenarios that require extremely high dimensional stability, such as high-precision telescopes, satellite optical systems, and laser equipment. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing ultra-low expansion optical glass to solve the problem that the traditional optical glass material has a high thermal expansion coefficient.
[0005] To achieve the above object, the present invention is implemented by the following technical scheme: A method for preparing ultra-low expansion optical glass comprises the following steps:
[0006] S1: Raw material selection:
[0007] Selecting oxide raw materials for the main components, including a matrix material with a low thermal expansion coefficient, auxiliary materials, and modifying materials for adjusting optical properties;
[0008] Introducing nano-sized oxide particles;
[0009] S2: Batching and Mixing:
[0010] Accurately weigh various oxide raw materials according to the designed proportions;
[0011] Use mechanical equipment to evenly mix the raw materials;
[0012] S3: Melting:
[0013] The mixed raw materials are melted at high temperature and homogenized by mechanical or ultrasonic means;
[0014] Provide gas protection to the melt during the melting process;
[0015] S4: Molding:
[0016] Cooling the molten glass material into shape;
[0017] Stretching or calendering of thin sheets or optical fibers;
[0018] S5: Annealing:
[0019] Performing preliminary annealing on the formed glass material;
[0020] S6: Doping and post-treatment:
[0021] Incorporating specific rare earth elements during raw material selection or melting;
[0022] Polish or coat the glass surface according to application requirements;
[0023] S7: Quality Inspection:
[0024] Measure the thermal expansion coefficient, refractive index, optical homogeneity and mechanical strength of glass.
[0025] Preferably, in the step S1, the selected matrix material is silicon dioxide, the content of which accounts for 70%-85% of the total mass, the auxiliary materials are aluminum oxide and zirconium oxide, the total amount of which is 10%-20%, and the modified material for adjusting the optical properties is titanium oxide, the content of which is 2%-5%;
[0026] The introduced nano-scale oxide particles include silicon dioxide or zirconium oxide, with a content of 0.5% to 3% and a particle size of 20 to 100 nanometers.
[0027] Preferably, in the step S2, a ball mill or a planetary mixer is used, the mixing time is 4-6 hours, and the temperature during the mixing process should be controlled at 20-30°C.
[0028] Preferably, in the step S3, the melting temperature is 1600-1700°C, the melting time is 8-12 hours, and the temperature fluctuation is controlled within ±5°C;
[0029] The mechanical stirring speed is 10-30rpm, the ultrasonic homogenization frequency is 20-40kHz, and the duration is 1-2 hours;
[0030] The gas protection during the melting process uses argon or nitrogen with a flow rate of 1-5L / min.
[0031] Preferably, in the step S4, the molten glass is poured into a mold preheated to 600-800°C, the cooling rate is 1-5°C / min, the stretching rate is 1-10 mm / s, and the rolling pressure is 0.1-1 MPa.
[0032] Preferably, in the step S5, the preliminary annealing temperature is 600-700°C, the time is 12-24 hours, and the temperature drop rate is 1-3°C / minute.
[0033] Preferably, in the step S6, the rare earth element is cerium oxide or lanthanum oxide, the doping content is 0.1%-1%, the polishing speed is 50-200 rpm, and the coating thickness is controlled at 100-500 nanometers.
[0034] Preferably, after the step S2, the selected oxide material is introduced into the melt by vapor deposition technology, the deposition rate of the selected oxide material is 0.01-0.1 micrometers / minute, and the gas pressure is 10^-3 to 10^-2Pa.
[0035] Preferably, after the S5 step, a multi-stage annealing treatment is performed to release the stress inside the glass to the maximum extent, the secondary annealing temperature of the multi-stage annealing is 400-500°C, the holding time is 4-8 hours, the final stage annealing temperature is 200-300°C, the holding time is 2-4 hours, and the final cooling rate is 0.5-2°C / minute.
[0036] The present invention provides a method for preparing ultra-low expansion optical glass, which has the following beneficial effects:
[0037] 1. The present invention precisely controls the chemical composition of glass (such as silicon dioxide, aluminum oxide, zirconium oxide, etc.) and introduces nano-scale oxide particles to make the glass have an extremely low thermal expansion coefficient (at the level of 10^-7 / ℃). This ultra-low thermal expansion coefficient ensures that the glass will hardly change in size under temperature changes, and is suitable for high-precision optical components and scientific instruments that need to maintain extremely high dimensional stability over a wide temperature range.
[0038] 2. The present invention uses nano-scale particles and homogenization technology (such as ultrasonic homogenization) to greatly improve the internal uniformity of glass and reduce optical defects. Optical uniformity (within λ / 10) ensures high light transmittance and low scattering loss of glass in optical applications, and is suitable for use in high-precision lenses, laser devices and astronomical telescopes.
[0039] 3. The introduction of auxiliary materials such as alumina and zirconia and the application of multi-stage annealing process in the present invention significantly improve the mechanical strength and hardness of the glass. The bending strength reaches 175-190MPa and the hardness reaches 6.3-6.7GPa, indicating that the glass has excellent impact resistance and wear resistance, so that it can still maintain stable performance in harsh mechanical environments.
[0040] 4. The present invention adjusts the refractive index and optical dispersion characteristics of the glass by adding titanium oxide and rare earth elements (such as cerium oxide and lanthanum oxide). The refractive index is between 1.48 and 1.52, which ensures that the glass has good optical focusing ability and low dispersion performance, making it excellent in precision optical imaging and laser transmission. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The present invention is a flow chart of the method for preparing the ultra-low expansion optical glass. DETAILED DESCRIPTION
[0042] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Please see attached Figure 1 The present invention provides a method for preparing ultra-low expansion optical glass, comprising the following steps:
[0044] S1: Raw material selection:
[0045] The oxide raw materials of the main components are selected, including a matrix material with a low thermal expansion coefficient, auxiliary materials, and a modifying material for adjusting the optical properties. The matrix material is usually high-purity silicon dioxide (SiO2), which accounts for 70%-85% of the total mass and is the main component of the glass, providing stable chemical properties and a low thermal expansion coefficient. Auxiliary materials include aluminum oxide (Al2O3) and zirconium oxide (ZrO2), with a total amount of 10%-20%. Aluminum oxide increases the mechanical strength and chemical stability of the glass, while zirconium oxide improves the crack resistance and hardness of the glass. The modifying material for adjusting the optical properties is titanium oxide (TiO2), which has a content of 2%-5%, which can increase the refractive index of the glass and improve its optical properties, especially in high-precision optical applications.
[0046] Introducing nano-sized oxide particles: Introducing nano-sized silica (SiO2) or zirconium oxide (ZrO2) particles into the formula, with a content of 0.5%-3%. The size of these particles is controlled between 20-100 nanometers, and their high surface area and unique physical properties are used to further reduce the thermal expansion coefficient of the glass and improve the uniformity and structural integrity of the material. Through technologies such as ultrasonic stirring or high-energy ball milling, ensure that these nanoparticles are evenly dispersed in the raw materials to avoid agglomeration.
[0047] S2: Batching and Mixing:
[0048] Accurately weigh various oxide raw materials according to the designed proportion: Use a high-precision electronic balance to weigh various raw materials according to the designed weight percentage to ensure that the proportion of each raw material is accurate and the error is controlled within ±0.01%.
[0049] Use mechanical equipment to mix the raw materials evenly: choose a ball mill or planetary mixer for mixing, and control the mixing time to 4-6 hours to ensure that all ingredients are fully mixed. During the mixing process, the ambient temperature should be controlled at 20-30℃ to avoid the raw materials absorbing moisture or reacting, which will affect the final quality and performance of the glass.
[0050] S3: Melting:
[0051] The mixed raw materials are melted at high temperature and homogenized by mechanical or ultrasonic means: the mixed raw materials are placed in a high temperature resistant platinum or ceramic crucible and melted in a high temperature furnace at 1600-1700℃ for 8-12 hours. The temperature fluctuation should be controlled within ±5℃ to ensure the uniformity of the melt. During the melting process, mechanical stirring (speed of 10-30rpm) or ultrasonic (frequency of 20-40kHz, duration of 1-2 hours) homogenization technology is used to further reduce bubbles and insolubles in the melt.
[0052] Gas protection for the melt during the melting process: Continuously fill argon or nitrogen above the melting process to prevent the melt from contacting the air, thereby avoiding the volatilization or contamination of oxides. The gas flow rate should be controlled at 1-5L / min to ensure that the melt surface is always covered by the protective gas.
[0053] S4: Molding:
[0054] Cooling the molten glass material into shape: slowly pour the molten glass material into a mold preheated to 600-800℃. The mold material is ceramic or high-temperature refractory metal to ensure uniform heat distribution during the molding process. The cooling rate of the molded glass should be controlled at 1-5℃ / minute to avoid the generation of internal stress.
[0055] Stretching or calendering of thin sheets or optical fibers: For glass that needs to be made into thin sheets or optical fibers, stretching or calendering operations are performed immediately after forming. The stretching rate should be 1-10mm / s, and the calendering pressure should be controlled at 0.1-1MPa to ensure that the finished product has good surface finish and internal uniformity.
[0056] S5: Annealing:
[0057] Perform preliminary annealing on the formed glass material: Place the formed glass in an annealing furnace, control the preliminary annealing temperature at 600-700℃, and the annealing time is 12-24 hours. During the annealing process, the temperature drop rate should be controlled at 1-3℃ / minute to slowly release the internal stress in the glass and prevent the glass from cracking or deforming due to a sudden drop in temperature.
[0058] S6: Doping and post-treatment:
[0059] Specific rare earth elements are added during the raw material selection or melting process: rare earth elements such as cerium oxide (CeO2) or lanthanum oxide (La2O3), and the doping amount is controlled at 0.1%-1%. The introduction of rare earth elements can enhance the weather resistance and UV resistance of glass without significantly affecting its optical properties.
[0060] Polish or coat the glass surface according to application requirements: During the polishing process, the polishing speed should be 50-200rpm to ensure that the glass surface reaches optical grade finish. The coating thickness is controlled at 100-500 nanometers, and advanced processes such as ion beam assisted coating technology (IBAD) are used to ensure that the coating layer is uniform and defect-free to achieve the best optical performance and anti-reflection effect.
[0061] S7: Quality Inspection:
[0062] Measuring the thermal expansion coefficient, refractive index, optical uniformity and mechanical strength of glass: Use high-precision instruments to test the key performance parameters of glass. The thermal expansion coefficient should be measured to below 10^-7 / ℃, and the test temperature range is -50℃ to 100℃ to ensure that the glass remains stable at different temperatures. The refractive index is required to be between 1.45-1.55, the optical uniformity must be within λ / 10 (λ=633nm), the bending strength should be 100-200MPa, and the hardness value is in the range of 5-7GPa to ensure its reliability and durability in practical applications.
[0063] In the preparation method of ultra-low expansion optical glass, the following key materials are used, each of which has a specific role:
[0064] 1. Silicon dioxide (SiO2)
[0065] Function: As the main matrix material, SiO2 is the basic component of optical glass, providing stable chemical properties and excellent optical properties. SiO2 has a low thermal expansion coefficient and high transparency, and is the basis for manufacturing high-quality optical glass.
[0066] Content: 70% - 85% of the total mass.
[0067] 2. Alumina (Al2O3)
[0068] Function: As an auxiliary material, Al2O3 increases the mechanical strength and chemical stability of glass, especially in high temperature and corrosive environments. It also helps improve the wear resistance and impact resistance of glass.
[0069] Content: Together with zirconium oxide, the total amount is 10% - 20%.
[0070] 3. Zirconium oxide (ZrO2)
[0071] Function: Zirconia is also an auxiliary material that provides high hardness and high crack resistance, significantly improving the durability and strength of glass. In addition, ZrO2 has a low coefficient of thermal expansion, which helps maintain the dimensional stability of glass.
[0072] Content: Together with alumina, the total amount is 10% - 20%.
[0073] 4. Titanium oxide (TiO2)
[0074] Function: As a modified material, TiO2 is used to adjust the refractive index and dispersion properties of optical glass. The addition of TiO2 can increase the refractive index of glass, giving it better focusing ability and imaging quality in optical applications.
[0075] Content: 2% - 5% of the total mass.
[0076] 5.Nano-scale silicon dioxide (nano-SiO2) or nano-scale zirconium oxide (nano-ZrO2)
[0077] Function: Nano-sized oxide particles are introduced to further reduce the thermal expansion coefficient of glass and improve its microstructure. The high surface area and unique physical properties of nanoparticles can increase the uniformity and mechanical strength of glass.
[0078] Content: 0.5%-3%.
[0079] Particle size: 20-100 nanometers.
[0080] 6. Rare earth elements (cerium oxide (CeO2) or lanthanum oxide (La2O3))
[0081] Function: Rare earth elements are used to enhance the optical properties and weather resistance of glass. CeO2 can improve the glass's UV resistance and prevent the glass from discoloring or degrading under UV light. La2O3 is used to increase the glass's refractive index, reduce light dispersion, and optimize optical transparency.
[0082] Doping amount: 0.1% - 1%.
[0083] 7. Gas protection (argon (Ar) or nitrogen (N2))
[0084] Function: Argon or nitrogen is used as a protective gas during the glass melting process to prevent the melt from contacting with oxygen in the air, avoiding oxidation reactions or other chemical contamination. This ensures the purity of the glass and the consistency of its composition.
[0085] Gas flow rate: 1-5L / min.
[0086] The following is an introduction in conjunction with specific embodiments:
[0087] Example 1
[0088] Raw material ratio:
[0089] Silicon dioxide (SiO2): 80%
[0090] Alumina (Al2O3): 10%
[0091] Zirconia (ZrO2): 8%
[0092] Titanium oxide (TiO2): 2%
[0093] Nano-silicon dioxide (nano-SiO2): 1%, particle size 50 nanometers
[0094] Rare earth elements: cerium oxide (CeO2) 0.5%
[0095] Process parameters:
[0096] Mixing: Use a ball mill to mix for 5 hours, and the temperature is controlled at 25°C.
[0097] Melting: The melting temperature is 1650°C, the melting time is 10 hours, and the temperature fluctuation is controlled within ±3°C.
[0098] Stirring: Mechanical stirring speed is 20 rpm, ultrasonic frequency is 30 kHz, and lasts for 1.5 hours.
[0099] Gas protection: Use argon gas with a flow rate of 3L / min.
[0100] Molding: The mold was preheated to 700°C and the cooling rate was 3°C / min.
[0101] Annealing: The initial annealing temperature is 650°C, the time is 18 hours, and the temperature drop rate is 2°C / min.
[0102] Post-processing: polishing speed is 100rpm, coating thickness is 300nm.
[0103] Example 2
[0104] Raw material ratio:
[0105] Silicon dioxide (SiO2): 85%
[0106] Alumina (Al2O3): 7%
[0107] Zirconia (ZrO2): 6%
[0108] Titanium oxide (TiO2): 2%
[0109] Nano-zirconia (nano-ZrO2): 2%, particle size 30 nanometers
[0110] Rare earth elements: lanthanum oxide (La2O3) 1%
[0111] Process parameters:
[0112] Mixing: Use a planetary mixer for 6 hours and control the temperature at 22°C.
[0113] Melting: The melting temperature is 1700°C, the melting time is 12 hours, and the temperature fluctuation is controlled at ±2°C.
[0114] Stirring: Mechanical stirring speed is 15 rpm, ultrasonic frequency is 25 kHz, and lasts for 2 hours.
[0115] Gas protection: Nitrogen is used with a flow rate of 2L / min.
[0116] Molding: The mold was preheated to 750°C and the cooling rate was 2°C / min.
[0117] Annealing: The initial annealing temperature is 670°C, the time is 20 hours, and the temperature drop rate is 2.5°C / min.
[0118] Post-processing: polishing speed is 150rpm, coating thickness is 400nm.
[0119] Example 3
[0120] Raw material ratio:
[0121] Silicon dioxide (SiO2): 75%
[0122] Alumina (Al2O2): 12%
[0123] Zirconia (ZrO2): 10%
[0124] Titanium oxide (TiO2): 3%
[0125] Nano-silicon dioxide (nano-SiO2): 0.5%, particle size 70 nanometers
[0126] Rare earth elements: cerium oxide (CeO2) 0.7%
[0127] Process parameters:
[0128] Mixing: Use a ball mill to mix for 4 hours, and the temperature is controlled at 28°C.
[0129] Melting: The melting temperature is 1600°C, the melting time is 8 hours, and the temperature fluctuation is controlled at ±5°C.
[0130] Stirring: Mechanical stirring speed is 25 rpm, ultrasonic frequency is 20 kHz, and lasts for 1 hour.
[0131] Gas protection: Use argon gas with a flow rate of 4L / min.
[0132] Molding: The mold was preheated to 650°C and the cooling rate was 4°C / min.
[0133] Annealing: The initial annealing temperature is 600°C, the time is 15 hours, and the temperature drop rate is 1.5°C / min.
[0134] Post-processing: polishing speed is 75rpm, coating thickness is 200nm.
[0135] Example 4
[0136] Raw material ratio:
[0137] Silicon dioxide (SiO2): 82%
[0138] Alumina (Al2O2): 8%
[0139] Zirconia (ZrO2): 8%
[0140] Titanium oxide (TiO2): 2%
[0141] Nano-zirconia (nano-ZrO2): 2%, particle size 40 nanometers
[0142] Rare earth elements: lanthanum oxide (La2O3) 0.5%
[0143] Process parameters:
[0144] Mixing: Use a planetary mixer for 5 hours and control the temperature at 24°C.
[0145] Melting: The melting temperature is 1680°C, the melting time is 9 hours, and the temperature fluctuation is controlled at ±4°C.
[0146] Stirring: Mechanical stirring speed was 18 rpm, ultrasonic frequency was 35 kHz, and lasted for 1.5 hours.
[0147] Gas protection: Nitrogen was used with a flow rate of 3 L / min.
[0148] Molding: The mold was preheated to 720°C and the cooling rate was 3°C / min.
[0149] Annealing: The initial annealing temperature is 680°C, the time is 16 hours, and the temperature drop rate is 2°C / min.
[0150] Post-processing: polishing speed is 125rpm, coating thickness is 350nm.
[0151] The following is a table of quality test results of the ultra-low expansion optical glass made based on the above examples. The table lists the measurement results of key performance indicators in each example, including thermal expansion coefficient, refractive index, optical uniformity, bending strength and hardness.
[0152] Table 1
[0153]
[0154] Among them, the table fields are explained as follows:
[0155] Thermal expansion coefficient: The thermal expansion coefficient of all examples is between 0.4 and 0.6×10^-7 / °C, which indicates that these glasses have extremely low dimensional changes when the temperature changes, which is one of the key properties of ultra-low expansion glass.
[0156] Refractive index: The refractive index was measured at 633 nm (red laser wavelength) and was between 1.48 and 1.52, indicating that the glass of each embodiment has good focusing ability and optical transparency in optical applications.
[0157] Optical uniformity: Optical uniformity is expressed in λ / 10, where λ is the wavelength (633 nm). The lower the uniformity value, the higher the optical quality of the glass. The uniformity of all examples is between 0.06 and 0.08λ / 10, showing very high optical uniformity.
[0158] Bending strength: The bending strength of the glass is between 175 and 190 MPa, indicating that these glasses have high mechanical strength and can resist large mechanical stress.
[0159] Hardness: The hardness is between 6.3 and 6.7 GPa, indicating that the glass has good wear resistance and durability.
[0160] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing ultra-low expansion optical glass, characterized in that: The following steps are involved: S1: Raw material selection: Selecting oxide raw materials for the main components, including a matrix material with a low thermal expansion coefficient, auxiliary materials, and modifying materials for adjusting optical properties; Introducing nano-sized oxide particles; S2: Batching and Mixing: Accurately weigh various oxide raw materials according to the designed proportions; Use mechanical equipment to evenly mix the raw materials; S3: Melting: The mixed raw materials are melted at high temperature and homogenized by mechanical or ultrasonic means; Provide gas protection to the melt during the melting process; S4: Molding: Cooling the molten glass material into shape; Stretching or calendering of thin sheets or optical fibers; S5: Annealing: Performing preliminary annealing on the formed glass material; S6: Doping and post-treatment: Incorporating specific rare earth elements during raw material selection or melting; Polish or coat the glass surface according to application requirements; S7: Quality Inspection: Measure the thermal expansion coefficient, refractive index, optical homogeneity and mechanical strength of glass.
2. The method for preparing ultra-low expansion optical glass according to claim 1, characterized in that: In the step S1, the selected matrix material is silicon dioxide, the content of which accounts for 70%-85% of the total mass, the auxiliary materials are aluminum oxide and zirconium oxide, the total amount of which is 10%-20%, and the modified material for adjusting the optical properties is titanium oxide, the content of which is 2%-5%; The introduced nano-scale oxide particles include silicon dioxide or zirconium oxide, with a content of 0.5% to 3% and a particle size of 20 to 100 nanometers.
3. The method for preparing ultra-low expansion optical glass according to claim 1, characterized in that: In the step S2, a ball mill or a planetary mixer is used, the mixing time is 4-6 hours, and the temperature during the mixing process should be controlled at 20-30°C.
4. The method for preparing ultra-low expansion optical glass according to claim 1, characterized in that: In the step S3, the melting temperature is 1600-1700°C, the melting time is 8-12 hours, and the temperature fluctuation is controlled within ±5°C; The mechanical stirring speed is 10-30rpm, the ultrasonic homogenization frequency is 20-40kHz, and the duration is 1-2 hours; The gas protection during the melting process uses argon or nitrogen with a flow rate of 1-5L / min.
5. The method for preparing ultra-low expansion optical glass according to claim 1, characterized in that: In the step S4, the molten glass is poured into a mold preheated to 600-800°C, the cooling rate is 1-5°C / min, the stretching rate is 1-10mm / s, and the rolling pressure is 0.1-1MPa.
6. The method for preparing ultra-low expansion optical glass according to claim 1, characterized in that: In the step S5, the preliminary annealing temperature is 600-700°C, the time is 12-24 hours, and the temperature drop rate is 1-3°C / minute.
7. The method for preparing ultra-low expansion optical glass according to claim 1, characterized in that: In the step S6, the rare earth element used is cerium oxide or lanthanum oxide, the doping content is 0.1%-1%, the polishing speed is 50-200rpm, and the coating thickness is controlled at 100-500 nanometers.
8. The method for preparing ultra-low expansion optical glass according to claim 1, characterized in that: After the step S2, the selected oxide material is introduced into the melt by vapor deposition technology, the deposition rate of the selected oxide material is 0.01-0.1 micrometers / minute, and the gas pressure is 10^-3 to 10^-2Pa.
9. The method for preparing ultra-low expansion optical glass according to claim 1, characterized in that: After the S5 step, a multi-stage annealing treatment is performed to release the stress inside the glass to the maximum extent. The secondary annealing temperature of the multi-stage annealing is 400-500°C, the insulation time is 4-8 hours, the final stage annealing temperature is 200-300°C, the insulation time is 2-4 hours, and the final cooling rate is 0.5-2°C / minute.